SYNTHESIS OF CARBON NANOTUBES BY THE ELECTRIC ARC-DISCHARGE METHOD - Yermagambet Bolat Toleukhanuly; Kazankapova Maira Kuttybaevna; Kassenova Zhanar Muratbekovna; Nauryzbaeva Asemay Turlangyzy (Academic Scientific Journal of Chemistry, 2020)
The paper presents the synthesis of carbon nanotubes (CNTs) by the method of electric arc-discharge. To obtain CNTs, the process of an electric arc-discharge of graphite was carried out; the current strength at a constant voltage of 50 V was 120, 150, 170, 200 A (inert medium - argon). Using the methods of electron microscopy, BET and Raman scattering, the chemical composition, specific surface area were determined, and the surface morphology of the obtained samples was studied. The results of determining the specific surface area and pore volume show that with increasing current strength, the specific surface area and specific pore volume increase from 25.450 to 159.737 m2 /g and from 0.011 cm3 /g to 0.068 cm3 / g, respectively. Electron microscopic images show CNT particles with a diameter of 58 to 370 nm, which are rolled into a single, seamless, cylindrical shape.